[tex]a = 3.(2) - \frac{8}{3} - \left( \frac{ ^{2)} 5}{6} + \frac{11}{12} \right) \cdot \frac{1}{3} \\ a = \frac{32 - 3}{9} - \frac{8}{3} - \left( \frac{10}{12} + \frac{11}{12} \right) \cdot \frac{1}{3} \\ a = \frac{29}{9} - \frac{ ^{3)} 8}{3} - \frac{21 }{12} \cdot \frac{1}{3} \\ a = \frac{29}{9} - \frac{24}{9 } - \frac{ {21}^{(3} }{36} \\ a = \frac{ ^{4)} 5}{ 9} - \frac{ ^{3)} 7}{12} \\ a = \frac{20}{36} - \frac{21}{36 } \\ \boxed{ \bold{a = - \frac{1}{36} }}[/tex]
Dan a determinat rezultatul corect.